What's New. Issue 1 (January 2014) - Unknown
WHAT'S NEW is provided as a service for our readers. It contains the latest news on the products, catalogs, tips, and supplies that manufacturers elect to highlight. Publication in WHAT'S NEW does no imply recommendation or endorsement by the Society for Applied Spectroscopy or the column editor. Contributions to WHAT'S NEW should be sent to Applied Spectroscopy, What's New Editor, 5320 Spectrum Drive, Suite C, Frederick, MD 21703 (Fax 301-694-6860; e-mailoffice@s-a-s.org ). Although there is no charge to submit materials, preference is given to Applied Spectroscopy advertisers. Call 913-712-8686 for questions regarding advertising.